Approaches to English for Specific and Academic Purposes Perspectives on Teaching and Assessing in Tertiary and Adult Education - Ennis, Michael; Prior, Jemma (bu,press, 2020)
This volume presents a selection of eight papers presented at three symposia on English for Specific Purposes (ESP) and English for Academic Purposes (EAP) that were held at the Free University of Bozen-Bolzano, Italy. The experiences detailed in the chapters offer a representative sample of the diversity of approaches to teaching and assessing ESP and EAP that were shared on those occasions. The contributions vary markedly by teaching and research context: whereas some report the results of meticulously planned research projects, others describe in detail cases embedded in specific contexts in Italy and in the US; others analyse the specialised language of particular discourses or domains, or reflect upon teaching methods and materials.